Castor leaf-shaped quasi-self-complementary antenna with dual band-rejection characteristics - Patre S.R.; Singh S.P. (My University, 2025)
In this paper, simulation study of single-sided castor leaf-shaped quasi-self-complementary antenna with dual band-rejection characteristics is presented for broadband applications. It provides broad impedance bandwidth of (2.2-13.0 GHz) which covers ultrawideband (UWB) spectrum and Bluetooth spectrums. Two different quarter-wavelength long resonators are used to reject overlapping WiMAX (3.3-3.8 GHz) and HiperLAN (5.15-5.35 GHz) bands. © 2015 IEEE.